Visual disorders associated with cerebral palsy. Issue 1 (January 1982) - Black, P
Abstract : School children severely afflicted with cerebral palsy, but unselected in regard to their visual status. have been studied. Of 120 children examined only 24 (20%) had normal eyes or ocular adnexae. Squint was found in 52.5% of the children and significant refractive errors in 50%. There was also a high incidence of strabismic and anisometropic amblyopia (15%) and visual field defects (11%). A number of other ocular abnormalities were found, the majority of which were not amenable to any form of treatment. Early identification of treatable ocular defects and their treatment along conventional lines is emphasised. It is also important to identify untreatable defects that may have a bearing on the child's education. These children need all the help available, and visual function should be at its best. A diagnosis of cerebral palsy has usually been made by the time such a child reaches 18 months of age. In view of the high incidence of ocular defects a full ophthalmological assessment should be part of the routine assessment of the child.